Cs2CdV2O6Cl2 and Cs3CdV4O12Br: two new non-centrosymmetric oxyhalides containing d0 and d10 cations and exhibiting second harmonic generation activity. Issue 28 (24th June 2019) - Li, Yanjun; Zhang, Dan; Liu, Lili; Zhang, Weiguo; Zhang, Jiang; Cong, Ye; Li, Xuanke; Halasyamani, P. Shiv
Abstract : Two new non-centrosymmetric oxyhalides containing d 0 and d 10 cations and exhibiting strong second harmonic generation activity. Abstract : Two new oxyhalides including d 0 and d 10 cations, Cs4 Cd2 V4 O12 Cl4 (1 ) and Cs3 CdV4 O12 Br (2 ), were successfully synthesized via a solid phase reaction. Their crystal structures have been determined by X-ray single crystal diffraction. Compound1 crystallizes in space group Cm (no. 8), whereas compound2 is found in space group Cmm 2 (no. 35). The corner-shared V3 O8 units and CdO2 Cl4 units in the compound1 bridge a three-dimensional network, whereas the corner-shared V4 O11 polyhedron and CdO4 Br2 octahedron in the compound2 form a three-dimensional structure. All the polar groups align in one direction, which results in a favorable net polarization. Powder second harmonic generation, using 1064 nm incident radiation, indicates that they are phase-matchable with observable and strong SHG response (5 and 7 times KH2 PO4, respectively). The UV-vis-NIR diffuse reflectance spectra indicate that the band gaps of the compound1 and2 are 3.00 eV (413 nm) and 3.13 eV (396 nm), respectively. Based on the IR and UV-vis-NIR data, the transparent range of both compounds is 0.4–10.4 μm. Furthermore, the electronic structure was also investigated by the first-principles calculations.